Role of Single-Photon Emission Computed Tomography Imaging in the Diagnosis and Treatment of Chronic Neck or Back Pain Caused by Spinal Degeneration: A Systematic Review - Varga, Michal; Kantorová, Lucia; Langaufová, Alena; Štulík, Jan; Lančová, Lucie; Srikandarajah, Nisaharan; Kaiser, Radek (World neurosurgery, 2023)
BACKGROUND: Chronic neck or back pain is a common clinical problem. The most likely cause is degenerative change, whereas other causes are relatively rare. There is increasing evidence on using hybrid single-photon emission computed tomography (SPECT) to identify the pain generator in spine degeneration. This systematic review explores the diagnostic and therapeutic evidence on chronic neck or back pain examined by SPECT. METHODS: This review is reported in accordance with the PRISMA guidelines. In October 2022, we searched the following sources: MEDLINE, Embase, CINAHL, SCOPUS, and 3 other sources. Titles and abstracts were screened and classified into diagnostic studies, facet block studies, and surgical studies. We synthesized the results narratively. RESULTS: The search yielded 2347 records. We identified 10 diagnostic studies comparing SPECT or SPECT/computed tomography (CT) with magnetic resonance imaging, CT, scintigraphy, or clinical examination. Furthermore, we found 8 studies comparing the effect of facet block intervention in SPECT-positive and SPECT-negative patients with cervicogenic headache, neck pain, and lower back pain. Five surgical studies describing the effect of fusion for facet arthropathy in the craniocervical junction, subaxial cervical spine, or the lumbar spine were identified. CONCLUSIONS: According to the available literature, a positive finding on SPECT in facet arthropathy is associated with a significantly higher facet blockade effect. Surgical treatment of positive findings has a good effect, but this has not been confirmed by controlled studies. SPECT/CT might therefore be a useful method in the evaluation of patients with neck or back pain, especially in cases of unclear findings or multiple degenerative changes.
Keywords: Degenerative disc disease; SPECT; Nuclear medicine; Facet block; bolesti zad; Humans; Intervertebral Disc Degeneration; Joint Diseases; degenerace meziobratlové ploténky; nemoci kloubů; bederní obratle; Back Pain; jednofotonová emisní výpočetní tomografie; Spinal fusion; Lumbar Vertebrae; bolest krku; Tomography, Emission-Computed, Single-Photon; Neck Pain; lidé